Development of hyaluronic acid-based electroconductive hydrogel as a sensitive non-enzymatic glucose sensor - AYCAN, DİDEM; KARACA ALBAYRAK, FATMA; ALEMDAR YAYLA, NESLİHAN (My University, 2023)
Herein, a novel hyaluronic acid (HA)-based electroconductive hydrogel with enhanced mechanical properties was developed for the non-enzymatic glucose detection. As the main component of the polymeric network, HA was modified through methacrylation to integrate photocrosslinkable groups into its backbone. Electrical conductivity was provided to hydrogel by using two different conductivity sources as the introduction of reduced graphene oxide (rGO) and polyaniline (PANI) to HA-based hydrogel structure. The combination of these conductivity sources not only provided the sufficient electrical conductivity (1.58 ×10−5 S/cm) to hydrogels, but also ensured superior mechanical performance in terms of compressive strength (992.1 kPa) and elastic modulus (23.4 kPa) due to the synergistic effect of the rGO and PANI, that are the significant parameters for sensor applications. The electrochemical activity and sensor performance of the HA-based hydrogel were investigated via cyclic voltammetry (CV) and choronoamperometry (CA) methods. The fabricated HA-based hydrogel sensor exhibited high sensitivity as 421.42 µAmM−1cm−2 and selectivity for glucose with a low detection limit (0.3 µM). Moreover, it showed excellent long-term stability, reproducibility and anti-interference feature towards uric acid, ascorbic acid and sorbitol. Based on these results it could be stated that the developed HA-based hydrogel sensor containing ternary HA-rGO-PANI formulation for the first time in the literature might be served as a promising potential for the non-enzymatic glucose detection and it also offers a new perspective for fabricating efficient hydrogel-based biosensing systems for future studies.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, KOMPOZİTLER; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, COMPOSITES; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Malzeme Kimyası; General Materials Science; Physical Sciences; Mechanics of Materials; Materials Chemistry; Electroconductive hydrogel; Glucose sensor; Hyaluronic acid; Polyaniline; Reduced graphene oxide